2019
DOI: 10.1111/plb.13008
|View full text |Cite
|
Sign up to set email alerts
|

Abiotic genetic adaptation in the Fagaceae

Abstract: Fagaceae can be found in tropical and temperate regions and contain species of major ecological and economic importance. In times of global climate change, tree populations need to adapt to rapidly changing environmental conditions. The predicted warmer and drier conditions will potentially result in locally maladapted populations. There is evidence that major genera of the Fagaceae are already negatively affected by climate change-related factors such as drought and associated biotic stressors. Therefore, kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 161 publications
0
13
0
Order By: Relevance
“…The potential outlier locus (FS_C1968) revealed by BayeScan is located in a sequence annotated as a putative auxin-response protein [18]. Auxin-response factors have been shown to be involved in abiotic adaptation (e.g., precipitation/drought, bud burst) in different tree species [44][45][46][47], and it has been proposed that beech morphology is related to environmental conditions at its growing sites [7,17]. Furthermore, Varsamis et al [48] detected significant differences in adaptive traits such as bud burst timing and survival under drought conditions between beech populations from West and East Rodopi in a provenance test and a growth chamber experiment.…”
Section: Discussionmentioning
confidence: 99%
“…The potential outlier locus (FS_C1968) revealed by BayeScan is located in a sequence annotated as a putative auxin-response protein [18]. Auxin-response factors have been shown to be involved in abiotic adaptation (e.g., precipitation/drought, bud burst) in different tree species [44][45][46][47], and it has been proposed that beech morphology is related to environmental conditions at its growing sites [7,17]. Furthermore, Varsamis et al [48] detected significant differences in adaptive traits such as bud burst timing and survival under drought conditions between beech populations from West and East Rodopi in a provenance test and a growth chamber experiment.…”
Section: Discussionmentioning
confidence: 99%
“…Common garden experiments and provenance trials have shown that local adaptation is common in forest trees being reflected in differences in adaptive phenotypic traits that match local environmental conditions [1][2][3][4][5] . Indeed, morphological and physiological data suggest that despite its presumed susceptibility to drought, populations of European beech from dry sites are more tolerant to drought than populations from wet sites [35][36][37][38] . For example, by monitoring physiological parameters such as leaf water potential and carbon isotopic discrimination during a 3 year period including the year 2003, one of the driest years in Europe, it was found that beech trees growing in a xeric Mediterranean environment did not demonstrate substantial signs of drought stress compared to beech trees in Central Europe 39 .…”
mentioning
confidence: 99%
“…C. sativa tree growth may be severely affected when the drought period is higher than two consecutive months ( Menéndez-Miguélez et al, 2015 ), with most probable negative consequences on the development of leaves and fruits ( Dinis et al, 2011a ). Drought response is complex to analyze, as it may be influenced by population history, frequency of drought events, and phenotypic plasticity ( Casasoli et al, 2006 ; Alcaide et al, 2019 ; Müller and Gailing, 2019 ).…”
Section: Abiotic Stresses Of C Sativamentioning
confidence: 99%